A review of novel methods of reducing oil absorption in fried food products - Reza Tahergorabi; Elham Ansarifar; Mitra Moodi; Zoya Tahergorabi (مجله دانشگاه علوم پزشکی بیرجند)
Deep fat frying is one of the oldest processes used to dry, cook, and formulate food products. The success of this process is due to its adaptability and flexibility in domestic and industrial scale. Fried foods are very popular owing to their good mouthfeel, high pleasantness, good taste, and texture. Foods absorb a significant amount of oil during frying, which increases the risk of such diseases as increased cholesterol levels, blood pressure, cardiovascular diseases, and cancer. The shift in consumer attitude and preference towards healthier options with lower fat content has markedly affected the fried food industry. Numerous attempts have been made globally to create low-fat products due to the excessive oil content in fried foods. There are novel methods to reduce the amount of oil in fried products. This review aimed to assess the effect of new technologies of blanching, microwave, and ultrasound on physicochemical properties, especially the reduction of oil absorption in fried products.